Information retrieval : 24th China Conference, CCIR 2018, Guilin, China, September 27-29, 2018, Proceedings /: 24th China Conference, CCIR 2018, Guilin, China, September 27-29, 2018, Proceedings. (2018) - Unknown
No abstract available